The application of fuzzy Delphi method for the development of STEM teaching model - Zeng, Zhaofeng; Li, Xin; Tho, Siew Wei (International Journal of Evaluation and Research in Education (IJERE), 2025)
In order to improve the ability of physics student teachers (PSTs) to teach using the science, technology, engineering, and mathematics (STEM) teaching model, this study applied the fuzzy Delphi method (FDM) to determine the constituent items that need to be included in the process of constructing the STEM teaching model according to the characteristics of PSTs. A questionnaire through literature review and expert advice was prepared, which contained 17 items in three constructs, including eight items for cultivating students’ abilities, four for teaching strategy design, and five for the expected outcomes. Then, the questionnaire was distributed to 16 experts to collect opinions and suggestions, which were analyzed and ranked using the FDM. The findings showed that all 17 items passed the expert consensus, all the specialist consensus values above 75%, the threshold values (d) ≤0.2, and the fuzzy scores (A) ≥α-cut value=0.5. Within the framework of the study and based on expert consensus, it is necessary for the newly developed STEM teaching model for PSTs to incorporate all 17 items across three constructs. This would optimally enhance the PSTs’ ability to employ the STEM teaching model in their teaching instruction.